2008
DOI: 10.1016/j.ejpain.2007.12.013
|View full text |Cite
|
Sign up to set email alerts
|

The Short‐Form McGill Pain Questionnaire as an outcome measure: Test–retest reliability and responsiveness to change

Abstract: Abilities of the Short-Form McGill Pain Questionnaire to assess change have scarcely been addressed in previous studies. The aim of the present study was to examine test-retest reliability, sensitivity to change and responsiveness to clinically important change using a Norwegian version (NSF-MPQ) in different groups of patients. ICC(1,1) values for test-retest reliability (relative reliability) assessed 1-3 days apart for total, sensory and affective scores were, respectively, 0.75, 0.76 and 0.62 in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 31 publications
6
98
1
1
Order By: Relevance
“…This supports the evidence that early diagnosis can improve outcomes [9,25]. Clinically important changes are represented in the QuickDASH as a change of 15 points [26]; WHODAS as 15 [27]; MPQ PRI as 5 with NRS as 3 [28]; FFI as 10 [21]. This sample shows significant clinical improvement across all measures 6 months after commencing physiotherapy.…”
Section: Discussionsupporting
confidence: 54%
“…This supports the evidence that early diagnosis can improve outcomes [9,25]. Clinically important changes are represented in the QuickDASH as a change of 15 points [26]; WHODAS as 15 [27]; MPQ PRI as 5 with NRS as 3 [28]; FFI as 10 [21]. This sample shows significant clinical improvement across all measures 6 months after commencing physiotherapy.…”
Section: Discussionsupporting
confidence: 54%
“…Another study 1 suggests that the VAS-24 may be more responsive than the VAS-now and MPQ for detecting changes in pain. A third study 2 found that the VAS and NSF-MPQ had high sensitivity in detecting improvement, but the VAS may more accurately reflect an unchanged or worsened condition than the NSF-MPQ. One challenge in Participants 76 active individuals who had lumbar discectomy, laminectomy, or fusion (55.4 ± 16.8 y of age).…”
Section: Implications For Practice Research and Future Educationmentioning
confidence: 99%
“…1 Similarly, the Norwegian Short-Form MPQ (NSF-MPQ) was developed to mirror the original MPQ measure through the inclusion of 15 common Norwegian pain descriptors. 2 The Visual Analog Scale (VAS) measures pain quantitatively by measuring the distance in millimeters from the left anchor of a 100-mm line to a mark made by the subject. The VAS-now and the VAS-24 are the same as the standard VAS form but refer to when the outcome measure is administered.…”
Section: Implications For Practice Research and Future Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…1; the remaining four are viewed as affective terms associated with experiencing pain [13]. The ordinal scale used to score the 15 terms comprises four levels [14]: 0 (no pain), 1 (mild pain), 2 (moderate pain), and 3 (severe pain).…”
Section: Short-form Mpqmentioning
confidence: 99%